Factors Associated with Non-Compliance of Medications in Hypertensive Patients - Khalid, Abdul; Ahemd, Imtiaz; Ahmed, Ashfaq; Rafique, Rubina; Arshad, Ali; Hamdani, Mazhar; Manzoor, Raza; Lone, Tahir; Riaz, Muhammad (International Journal of Pathology, 2018)
Objectives: To determine different factors associated with non-compliance to anti-hypertensive medications.Methods: Patients diagnosed as suffering from hypertension and either taking or had taken treatment in the pastwere included in the study. Study Questionnaires was filled by investigators (consultants, Registrars and PGstudents) during face to face clinical encounters with hypertensive patients who had been non-compliant to antihypertensivemedications. Statistical analysis was performed by using SPSS-21 software. Factor analysis wasperformed for assessing the validity of the responses for the 20 items present in the questionnaire for a samplecomprising of 300 hypertensive patients.Results: The Principal Component Extraction Analysis showed several factors associated with non-complianceto medications. Some patients did not have easy access to their treating physician (0.83) while others did not haveany significant change or improvement in their health by using anti-hypertensive medication (0.83). LongDistance from health facility (0.75), difficulty in sparing time (0.74), polypharmacy (0.70), lack of symptoms (0.67),forgetfulness (0.67), high cost of the treatment (0.59), undesirable side effects of anti-hypertensive drugs (0.50) andlack of family support (0.45) were contributing towards non-adherence to antihypertensive treatment in thiscohort of patients.Conclusion: There are number of factors associated with non-compliance of anti-hypertensive medications. Theknowledge of these factors will help to develop effective interventions with deeper understanding to overcomethe non-compliance in hypertensive patients.